Parâmetros espirométricos e níveis de IFN-y e IL-5 no escarro induzido de pacientes com asma ou rinite alérgicas - Marra, Sheila Mara Gonçalves (2007)
Asthma and allergic rhinitis are mediated by IgE antibodies through the development of allergen-specific Th2 cells in genetically predisposed and sensitized subjects. Asthma and rinithis are frequently associated, suggesting the concept of one airway, one disease . The aims of this study were to analyze spirometrics parameters and IFN-γ and IL-5 levels in the induced sputum from patients with asthma or allergic rhinitis (AR) and non-atopic subjects. Thirty-three subjects aged 18 to 60 years, both sexs, were analyzed. From these, eight were asthmatics and 16 had allergic rhinitis (AR), and both groups had positive skin prick test (SPT) to aeroallergens. The nine remaining subjects were healthy non-atopics with negative SPT to aeroallergens. Spirometry was performed through evaluating the forced vital capacity (FVC), forced expiratory volume in the first second (FEV1) and forced expiratory flux between 25 and 75% (FEF25-75%) pre and post-bronchodilators. Induced sputum samples were collected and IFN-γ and IL-5 levels were quantified by immunoassays. Significant pre- and post-bronchodilator variation was observed only for FEV1 with higher values in asthmatics compared to patients with RA and non-atopics. There was no significant difference in pre- and post-bronchodilator parameters among the three groups, although there was a tendency for pre-bronchodilator lower FEF25-75% values in asthmatic patients. IFN-γ levels in the induced sputum showed no significant difference between the groups but, IL-5 levels were higher in patients with asthma and AR compared to non-atopics. It can be concluded that Spirometric alterations were not able to predict the occurrence of broncoconstriction in patients with AR, but predominant IL-5 levels in the induced sputum of these patients reinforce the role of the Th2-type immune response in low respiratory airways that could contribute to the development of asthma in patients with AR.